Analisis Push And Pull Motivation Factors Terhadap Minat Berkunjung Wisatawan Ke Kabupaten Karangasem, Bali - Desak Made Febri Purnama Sari; Safitri, Ni Komang; Widiantari, Komang Sri; Wita Indrayani, I Gusti Ayu Putu (JURNAL BISNIS HOSPITALITI, 2025)
Research purposes to identify the factors influencing tourists' interest in visiting Karangasem Regency, Bali.  A quantitative data analysis was conducted involving 192 domestic tourists visiting Karangasem Regency. The data were analyzed using Confirmatory Factor Analysis (CFA) in SPSS version 25. The analysis revealed that from the initial 32 indicators tested, three main factors emerged that can explain the interest in visiting Karangasem Regency: "peak travel experience," "social bonding," and "retreat." This research identifies that these factors play a significant role in influencing tourists' interest in visiting Karangasem Regency, Bali. The findings are expected to enrich the understanding of push and pull factor analysis regarding tourists' interest in visiting Karangasem, Bali. Furthermore, this study serves as a reference for authors and readers in the future development of tourism marketing management knowledge.